MUTU FISIK, KIMIA DAN ORGANOLEPTIK KUE PUKIS DENGAN PERBANDINGAN TEPUNG TERIGU DAN TEPUNG PISANG KEPOK ENGGANO (Musa acuminata x balbisiana) - Marsigit, Wuri; Susanti, Laili; Avin Nazkia, Varizka (BPFP Faperta UNIB, 2024)
This study aims to determine the effect of a composition of wheat flour and Enggano banana flour on the physical, chemical and organoleptic properties of pukis cake. The experimental design used was a completely randomized design (CRD) with a single factor, namely the composition of wheat flour and Enggano banana flour (100%:0%, 90%:10%, 80%:20%, 70%:30%, 60%:40%) carried out with 3 replications. The results showed that the composition of wheat flour and Enggano banana flour had a significant effect on water content, texture, swelling power, and ash and fiber content. The texture and swellability decreased with increasing Enggano banana flour used. On the other hand, ash content and fiber content were higher. The color of the pukis cake became darker with increasing Enggano banana flour used. The used of 30% kepok Enggano banana flour was the best treatment with the panelist's preference for color shows a value of 3.04 (like), aroma 3.80(like-very like), taste 3,48 (like-very like), texture 3.32 (like-very like), and over all 3.64 (like-very like).